PENGARUH MODEL INKUIRI BERBANTUAN ALAT PERAGA EDUKATIF TERHADAP LITERASI SPASIAL - Yustitia, Via (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
Spatial literacy is related to the ability to use mathematics related to geometry. Prospective elementary school teachers need to master spatial literacy. However, the spatial literacy of PGSD students is still unsatisfactory. One of the lecturers' efforts to improve the quality of learning. An inquiry-assisted inquiry model of educational props can be an alternative. The purpose of this study is to determine whether the inquiry model assisted by educational teaching aids influences spatial literacy. This research is a quasi-experimental study with the population of semester I PGSD students in 2019/2020. Through purposive sampling, researchers chose class D as the experimental class and class F as the control class. Data obtained through the test method. Data analysis uses a mean different test. The results showed that there was an influence of the inquiry model assisted by educational teaching aids on spatial literacy.